Use of Ginger and Turmeric Rhizomes to Control Fusarium Wilt Disease (Fusarium sp.) in Shallot Plants (Allium cepa L.) - Husda Marwan; Mulyati Sri; Rani Inda Mawadah (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2026)
Fusarium sp. is a soil-borne pathogen that causes Fusarium wilt, a disease that reduces shallot productivity. The control of this disease still relies on the use of synthetic fungicides, which have negative impacts on the environment and human health. This study aims to evaluate the potential of ginger and turmeric rhizome solutions as a means of controlling Fusarium wilt in shallot plants. A Completely Randomized Design (CRD) was used in this study, consisting of six treatments, including a positive control (synthetic fungicide) and a negative control (no treatment). The results showed that ginger and turmeric rhizome solutions have potential in controlling Fusarium wilt disease in shallot plants. This study provides new insights into environmentally friendly alternatives for plant disease management and can help farmers sustainably increase shallot productivity.